2012
DOI: 10.5897/ajmr11.1384
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal activity of Calocybe gambosa extracts against yeasts and filamentous fungi

Abstract: Three strains of Calocybe gambosa (Fr.) Donk were investigated as possible sources of biologically active substances with antifungal activity. After submerged cultivation of C. gambosa mycelium, biologically active materials were isolated as ethyl acetate extracts from culture liquids. The in vitro activity of these C. gambosa extracts (Cg1, Cg2, Cg3) against yeasts and filamentous fungi was evaluated using the Clinical and Laboratory Standards Institute (CLSI) M27-A2 and M38-A2. The minimum inhibitory concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…oxidant potential of St. George mushroom. Previously, several authors reported the antioxidant potential of C. gambosa[Angelini et al, 2012;Barroetaveña & Toledo, 2017;Vaz et al, 2011], though results of their investigations indicate its lower antioxidant potential compared to the sample analyzed in this study. Furthermore, a comparative antioxidant activity analysis of ethanolic and water extract with soluble polysaccharides conducted byVaz et al [2011]…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…oxidant potential of St. George mushroom. Previously, several authors reported the antioxidant potential of C. gambosa[Angelini et al, 2012;Barroetaveña & Toledo, 2017;Vaz et al, 2011], though results of their investigations indicate its lower antioxidant potential compared to the sample analyzed in this study. Furthermore, a comparative antioxidant activity analysis of ethanolic and water extract with soluble polysaccharides conducted byVaz et al [2011]…”
contrasting
confidence: 57%
“…fungal strains [Angelini et al, 2012]. Among the tested strains, C. albicans (DBVPG 4268) strain turned out to be the most susceptible to the activity of the extract.…”
Section: Antimicrobial Activity Of C Gambosa Extractmentioning
confidence: 99%